Droplet Microarrays: From Surface Patterning to High‐Throughput Applications. Issue 20 (23rd March 2018) - Feng, Wenqian; Ueda, Erica; Levkin, Pavel A.
Abstract: High‐throughput screening of live cells and chemical reactions in isolated droplets is an important and growing method in areas ranging from studies of gene functions and the search for new drug candidates, to performing combinatorial chemical reactions. Compared with microfluidics and well plates, the facile fabrication, high density, and open structure endow droplet microarrays on planar surfaces with great potential in the development of next‐generation miniaturized platforms for high‐throughput applications. Surfaces with special wettability have served as substrates to generate and/or address droplets microarrays. Here, the formation of droplet microarrays with designed geometry on chemically prepatterned surfaces is briefly described and some of the newer and emerging applications of these microarrays that are currently being explored are highlighted. Next, some of the available technologies used to add (bio‐)chemical libraries to each droplet in parallel are introduced. Current challenges and future prospects that would benefit from using such droplet microarrays are also discussed. Abstract : Parallelization and miniaturization of experiments are fundamentally important in biology, chemistry, the pharmaceutical industry, biotechnology, medicine, and diagnostics. The formation of droplet microarrays with designed geometry on chemically prepatterned surfaces is described and some of their emerging applications in cell biology, microbiology, biotechnology, materials science, and chemistry are highlighted.